(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The transmission system line is one of the most important aspects of the overall network. Transmission lines transport a huge amount of energy. The demand for energy as well as its delivery has grown substantially in recent years, and a distribution system’s primary function is to carry electrical current from an initial location to utility grid. The greater emphasis on preventing electricity attenuation has resulted from the explosion between limiting output and a huge claim. In long distance networks, line inefficiencies, as well as speculative aspects such as physical losses and various technical losses, are substantial. Generally, investigation of failure of system is a highly focused topic in power systems development to remove fault in such a brief time and re-establish power station as fast as feasible with the least amount of disruption. However, detecting a failure that affects the transmission line is a difficult process since it requires both investigating the fault and enhancing the system’s dependability. Considering all of the characteristics that interconnect the entire power system, the transmission line is vulnerable. The goal of this research is to examine transmission line breakdown protection.